Relative age effects in women`s ice hockey: Contributions of body size and maturity status - Geithner, C. A.; Molenaar, C. E.; Henriksson, T.; Fjellman-Wiklund, A.; Gilenstam, K. (Women in Sport and Physical Activity Journal, 2018)
obtained, and BMI and chronological age were calculated for each player. Players recalled age at menarche, and maturity status was classified as early, average, or late relative to population-specific means. Chi-square (X2), Odds Ratios (OR), 95% Confidence Intervals (CI) and effect sizes (Cohen`s w) were calculated using population data across quartiles and for pairwise comparisons between quartiles. Descriptive statistics and MANOVAs were run by quartile and by country. Significant RAEs were found for Canadian players across quartiles (p < .05), along with a Q2 phenomenon (Q2: Q3, Q2: Q4, p < .05). Swedish players were overrepresented in Q3 (Q3: Q4, p < .05). Q4 was significantly underrepresented in both countries (p < .05). The oldest, earliest maturing, and shortest players in both countries were clustered in Q2; whereas the next oldest and latest maturing Swedish players were found in Q3. Age, physical factors, and interactions may contribute to overrepresentations in Q2 and Q3. These findings do not suggest the same bias for greater relative age and maturity found in male ice hockey.